1975
DOI: 10.1139/m75-269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc-smelter emissions on forest soil microflora

Abstract: Within 2 km of a zinc (Zn) smelter in Palmerton, Pennsylvania, near the Lehigh Water Gap, up to 13.5% Zn by weight has been measured in the O2 horizon of the soil, and up to 8% Zn in the A1 horizon. The total numbers of bacteria, actinomycetes, and fungi (measured by dilution plate counts) were greatly reduced in the most severely Zn-contaminated soils compared with control soils. The reduction of microbial populations may be a partial cause of the decreased rate of litter decomposition at Lehigh Gap. Growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
2

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(52 citation statements)
references
References 4 publications
3
47
0
2
Order By: Relevance
“…Experiments showed that the number of bacteria in the rhizosphere of (Brookes and McGrath, 1984;Chander and Brookes, 1991;Jordan and LeChevalier, 1975;Konopka et al, 1999). Besides, the microorganism community structure of the rhizosphere population is important in the context of plant growth.…”
Section: Plant-growthmentioning
confidence: 99%
“…Experiments showed that the number of bacteria in the rhizosphere of (Brookes and McGrath, 1984;Chander and Brookes, 1991;Jordan and LeChevalier, 1975;Konopka et al, 1999). Besides, the microorganism community structure of the rhizosphere population is important in the context of plant growth.…”
Section: Plant-growthmentioning
confidence: 99%
“…Nas concentrações inferiores a 100 µM, o zinco é considerado elemento essencial para o crescimento de fungos (Ross 1975). A partir desta dosagem, o zinco geralmente causa efeitos prejudiciais acentuados sobre a vegetação e a microbiota (Jordan & Lechevalier 1975).…”
Section: Resultsunclassified
“…O efeito seletivo dos metais pode resultar na substituição de diversas espécies e no estabelecimento de uma micota terrestre resistente ou tolerante (Jordan & Lechevalier 1975). A presença de determinado metal no solo representa, assim, mais um parâmetro a ser levado em consideração na compreensão das interações competitivas que contribuem para a composição da micota terrestre.…”
Section: Introductionunclassified
“…Huysman et al, 1994). Jordan and Lechevalier (1975) found a decrease of between one to two orders of magnitude in numbers of bacteria along a Zn pollution gradient while fungi and actinomycetes were less affected. Dar (1996) studied the effect of added Cd and found greater diversity of fungi and higher bacterial populations in control than in the Cd treated soil.…”
Section: Soil Microbial Diversitymentioning
confidence: 98%
“…Some species might be eliminated while others may appear in larger numbers because of reduced competition for substrate. Jordan and Lechevalier (1975) reported that microbial populations in soils close to a zinc-smelter contained greater proportions of bacteria able to grow on media containing high concentration of Zn. Several authors have found that, within the bacterial community, metals are more toxic to Gram-positive than the Gram-negative bacteria (Barkay et al, 1985).…”
Section: Soil Microbial Diversitymentioning
confidence: 99%